Peran UNDP Dalam Mengatasi Permasalahan Kekerasan Terhadap Perempuan di Sudan Selatan Melalui Program UNSCR 1325 - Resita Yuana, Ni Made; Sushanti, Sukma; Widya Nugraha, A.A Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2018), 2018)
ABSTRACT As a new independent nation, the rate of violence against women in South Sudan is quiet high. One of the reasons for this incident is the legacy of the conflict before the independence of southern Sudan. The high level of violence against women in South Sudan managed to steal the attention of the world including the United Nations. UNDP (United Nations Development Program) works with the South Sudan’s government to address this issue. One of the strategies used is UNSCR 1325 (United Nations Security Council Resolution) program. Addressing the problem of how UNDP's role in helping address the issue of violence against women in South Sudan through the UNSCR program 1325, this study aims to analyze the role of UNDP as an international organization in a domestic issue of a country where the country with the government as its highest capacity has failed to provide protection to its citizens, especially women. The concept which used in this study is the role and function of international organizations and it is not intended to show the success or failure of the program applied. This study uses a descriptive qualitative method using official documents issued by the governments of South Sudan and the United Nations as data sources. Keywords: international organization, South Sudan government, gender-based violence, women, UNDP, UNSCR1325.